Asimmetrija strukturny pojasa verchnich konecnostej i ee projavlenie v tennisnom udarnom dejstvii - Ivanova, G. P.; Spiridonov, D. V.; Sautina, E. N. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The search of forms of the optimum coordination of individual properties of the impellent systems participating in the realization of concrete actions, with their general biomechanical regularities is one of the major problems of sports practice. The account of features of asymmetry in the organization of movements helps to form complex coordinated motor actions adequate as much as possible to the human nature.